FORMATION OF PUPILS' CIVIС CONSCIOUSNESS IN THE CONDITIONS OF THE EDUCATIONAL PROCESS OF PRIMARY SCHOOL - Danyliak, R.Z.; Komarchyn, N.R. (Sworld-Us Conference proceedings, 2025)
The national orientation of modern education system is characterized. The main aspects of civic consciousness as one of the forms of the consciousness of personality are elucidated. The importance of the formation of civic consciousness in the system of n